Stable π-π Dependent electron conduction band of TPP[M(Pc)L 2]2 molecular conductors (TPP = tetraphenylphosphonium; M = Co, Fe; Pc = phthalocyaninato; L = CN, Cl, Br) - Yu, Derrick Ethelbhert C. (Animo Repository, 2011)
The partially-oxidized TPP[M(Pc)L2]2 molecular conductors exhibit variable electronic and magnetic transport bulk materials properties due to central metal and axial ligand molecular modifications. The controllable electrical conductivity and giant negative magnetoresistance can be mainly attributable to the varying ligand field energy and physical bulkiness of the axial ligands which cause modulation in the intra-molecular π-d (Pc-M) and inter-molecular π-π (Pc-Pc) interactions in the TPP[M(Pc)L 2]2 system, respectively. Characterization of the electronic conduction band utilizing one-dimensional (1-D) tight-binding approximation from infrared reflectance and thermoelectric power profile reveal consistent band widths of 0.43 eV-0.62 eV for the Co series (L = Br < Cl < CN) and 0.44-0.56 eV for the Fe series (L = Br < Cl < CN). The fixed band width suggests that stable electron conduction bands (transport pathway) can be constructed which can withstand the molecular π-d interaction modifications that severely alter the bulk electronic and magnetic materials properties of the TPP[M(Pc)L2]2 molecular conductors. © 2011 The Royal Society of Chemistry.